Active and healthy ageing logistics: Sabugal’s case - Dias, Márcia (2016)
Active and healthy ageing logistics aims to improve the quality of life of ageing population through a platform that will promote efficient health and social care to the customer. Indeed, this plataform will anticipate customer wants and optimize the service producing a network to fulfil customer needs. Active and healthy ageing will focus on the living process undergone by a citizen during his lifetime. This can be influenced by various factors such as the living environment, as well as the genetic and psychological factors that contribute to the health status of the elderly. The research is descriptive, explanatory and unique. It is based on literature review of the normative and legal framework applied to entities addressing prevention, healthcare and social support. It will also try to emphasize the societal changes as the outcome of new legislation compared to previous regulations. An exhaustive factual analysis of the content of the disclosure provided in the Annual Reports published by entities from the Council of Sabugal will be presented. The empirical analysis is supported on the 25 entities classified as SME, which are the object of this research from the Council of Sabugal. This entities address the social response offer to the society and the activities especially indicated to active and elderly people that suffer from common pathologies in ageing and rehabilitation paths.